2021
DOI: 10.1590/1807-1929/agriambi.v25n5p305-311
|View full text |Cite
|
Sign up to set email alerts
|

Allometric relationship and leaf area modeling estimation on chia by non-destructive method

Abstract: This study aimed to obtain equations to estimate leaf area from linear leaf dimensions and establish the allometric relationship between leaf area and the number of leaves on the main stem of chia (Salvia hispanica L.) at different sowing times. The experiment was conducted in the agricultural year 2016/2017 on five sowing times in Santa Maria, RS, Brazil, in a randomized block design with four repetitions. In each plot, ten random plants were marked weekly during the vegetative phase to determine the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…The present study showed that the best equations to estimate the LA of peanut cultivars were those that used LW, compared to equations that used only one leaflet dimension (L or W), with the best criteria and adjustments of the models used (Guimarães et al 2019, Macário et al 2020, Goergen et al 2021, except for the exponential model, in which the best equations were those that used L of the leaflets (Ribeiro et al 2020).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The present study showed that the best equations to estimate the LA of peanut cultivars were those that used LW, compared to equations that used only one leaflet dimension (L or W), with the best criteria and adjustments of the models used (Guimarães et al 2019, Macário et al 2020, Goergen et al 2021, except for the exponential model, in which the best equations were those that used L of the leaflets (Ribeiro et al 2020).…”
Section: Discussionmentioning
confidence: 81%
“…Generally, linear models are the most used to estimate the leaf area of agricultural and forest species (Gomes et al 2020, Goergen et al 2021, Hernandéz-Fernandez et al 2021, Mela et al 2022). However, it is assumed that these models are used with losses in precision, which often occurs due to the high values of the intercepts (β0) of the regression line (Santos et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The models presented coefficient of determination (R²) values of above 0.86, indicating that at least 86% of the variations in sapodilla LA were explained by the equations proposed for the estimation (Table 1). The equations that used the LW value presented the best criteria for estimating the LA of the species, giving the best fits of the regression models (Macário et al, 2020;Goergen et al, 2021). The exception was the exponential model, where the best criteria were observed in the equation in which the WW value was used (Ribeiro et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The determination coefficients (R²) of the equations obtained were higher than 0.83, indicating that at least 83% of the variations observed in the leaf areas of T. populnea were explained by the models constructed using linear dimensions of the leaf limbs. The allometric equations that were obtained from the product between length and width (LW), compared to those that employed L or W, provided the greatest adjustments to the regression models (Guimarães et al 2019, Goergen et al 2021, Lucena et al 2021, Cargnelutti Filho et al 2021, Toebe et al 2021, as well as the best criteria to satisfactorily estimate the leaf area of T. populnea, except for the cubic model, in which the best equation was obtained using the product between length and length of leaf limbs (LL).…”
Section: Discussionmentioning
confidence: 99%